Assessment of Turbulence Models for Flow Simulation around a Wind Turbine Airfoil. (22nd March 2011) - Villalpando, Fernando; Reggio, Marcelo; Ilinca, Adrian
Abstract : This investigation focuses on the application of the computational fluid dynamics tool FLUENT to the study of flows over the NACA 63–415 airfoil at various angles of attack. With the aim of selecting the most suitable turbulence model to simulate flow around ice-accreted airfoils, this work concentrates on assessing the prediction capabilities of various turbulence models on clean airfoils at the large angles of attack that cause highly separated flows to occur. The study was undertaken by conducting simulations with the one-equation Spalart-Allmaras (SA) model, the two-equation RNGk - ϵ and SSTk - ω models, and the Reynolds stress model (RSM). Domain discretization was carried out using general quadrilateral grids generated with GAMBIT, the FLUENT preprocessing tool. Comparisons were made with available experimental data.